Good Practice Note on Dam Safety - World Bank (World Bank, Washington, DC, 2021)
The objective of this good practice note (GPN) on dam safety is to provide additional guidance to World Bank staff on the application of relevant requirements under the environmental and social framework (ESF). This GPN provides guidance on using a risk management approach to the application of the dam safety requirements. The guidance contained in this note is designed to enhance the quality of practice without creating new requirements for the application of the ESF. The GPN provides guidance on compliance requirements, a risk management approach to dam safety, risk analysis tools, quality of information and capacity, application to World Bank operations, and procedural aspects. The GPN pertains to: (a) construction of new dams or dams under construction (DUC) under investment project financing (IPF); (b) rehabilitation of existing dams under IPF; and (c) existing dams or DUC that are not financed under IPF, on which the project relies or may rely.